Development Of Trichokompos In Empowering Mekar Tani Farmer Groups In Nagari Piobang, Lima Puluh Kota Regency, West Sumatra: Pengembangan Trichokompos Dalam Pemberdayaan Kelompok Tani Mekar Tani Di Nagari Piobang, Kabupaten Lima Puluh Kota, Sumatera Barat - Sri Indrayati; Suryani; Elsa Widia; Syamsuwirman; Butsainah Jauharah Taqiyyah; Resi Ria Lestari (Journal of Community Service and Application of Science, 2023)
Farmer Group "Mekar Tani" is one of the farmer groups in Jorong Gando, Nagari Piobang, Payakumbuh District, Lima Puluh Kota Regency, West Sumatra with 20 members. The scarcity of subsidized inorganic fertilizers and farmers' dependence on the use of inorganic fertilizers are problems in efforts to increase the production of group agricultural products. In early 2023, this farmer group is determined to start producing compost on a small scale. Due to limited knowledge and skills, members of this farmer group are still not proficient in producing quality compost. As in the procurement of raw materials and decomposers, almost entirely purchased it requires high production costs. In making compost can utilize the resources around these partners, such as husks, cocoa skins, and cow/chicken dung which are agricultural and livestock waste from members of this group.  In addition, the production entirely uses manual equipment so the results are also not optimal. So community service activities were carried out in the form of training and assistance in making Trichocompost. Trichokompos is a compost containing Trichoderma sp mushrooms, which was developed as an alternative to environmentally friendly fertilizers in increasing productivity independently and increasing partner skills. This training can improve the knowledge and skills of Mekar Tani farmer groups on making Trichocompost as measured through questionnaires to achieve an increase of 87%.